2016
DOI: 10.7567/jjap.55.080306
|View full text |Cite
|
Sign up to set email alerts
|

Tunable schottky barrier in blue phosphorus–graphene heterojunction with normal strain

Abstract: The graphene–blue phosphorus van deer Waals (vDW) heterojunction was studied by using density functional theory. Our calculations reveal that the intrinsic electronic structure of blue phosphorus and graphene is well preserved and forms an n-type schottky barrier at equilibrium state. With increasing of normal tensile strain, the n-type is well kept. With compressive strain, the Dirac cone of graphene gradually shifts from conduction band minimum to valance band maximum of blue phosphorus, leading a turning of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 44 publications
(51 reference statements)
0
10
0
1
Order By: Relevance
“…Most recently, there has been rapidly growing interest in atomic-scale vertical van der Waals (vdW) heterostructures made from a combination of G and other 2D semiconducting materials, such as G/MoS 2 37 40 , G/phosphorene 41 45 , G/arsenene 46 , 47 , G/blue phosphorene 48 , 49 , and G/g-GaN 50 . Such heterostructures preserve the unique Dirac cone structure of G and provide a higher electronic quality for G-based nanodevices.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, there has been rapidly growing interest in atomic-scale vertical van der Waals (vdW) heterostructures made from a combination of G and other 2D semiconducting materials, such as G/MoS 2 37 40 , G/phosphorene 41 45 , G/arsenene 46 , 47 , G/blue phosphorene 48 , 49 , and G/g-GaN 50 . Such heterostructures preserve the unique Dirac cone structure of G and provide a higher electronic quality for G-based nanodevices.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] For example, monolayer graphene remains a zero-gap material under an external electric field but a finite band gap appears for bilayer and multilayer graphene. 18,19 Because of the impressive progress in graphene research, enormous scientists have focused on exploring other 2D materials.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the difficulties in conducting the above-mentioned experimental studies, theoretical techniques such as first principle calculations, which are based on the laws of quantum mechanics and calculate the mechanical, electronic, optical, and magnetic properties of materials using only fundamental physical constants, [128] and molecular dynamics (MD) simulations, which study the equilibrium and transport properties of a classical many-body system by solving Newton's equations of motion based on empirical data, [129] are frequently adopted to investigate the influence of external strain on the interlayer coupling of various vdW heterostructures. [130][131][132][133][134][135][136][137][138][139][140][141][142] Besides the good controllability, theoretical methods could also uncover the underlying modulation mechanisms. For example, by using time-domain ab initio MD simulation, Tian et al [143] demonstrated that the electron-transfer dynamics in MoS 2 /WS 2 vdW heterostructure could be efficiently tuned by external strain, due to the reduction of energy in the K valley, which would block the original K-to-T valley electron-transfer route.…”
Section: External Strain/pressure Fieldmentioning
confidence: 99%